2014
DOI: 10.1007/s13277-014-2045-3
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SOX2 promotes migration, invasion, and epithelial-mesenchymal transition through the Wnt/β-catenin pathway in laryngeal cancer Hep-2 cells

Abstract: SOX2 is a high-mobility group box containing transcription factor essential for the maintenance of embryonic stem cells. Recent evidence indicates that SOX2 overexpression correlates with metastasis and poor prognosis in patients with laryngeal squamous cell cancer. To investigate how SOX2 contributes to this aggressive phenotype, we introduced the human SOX2 gene into a low SOX2-expressing human laryngeal cancer cell line Hep-2. Cell migration and invasion were determined by the Transwell assay with or withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 25 publications
5
56
0
Order By: Relevance
“…Here we demonstrate that SOX2 overexpression influences the migratory potential of NT2/D1 cells, derived from the metastasis of a human testicular germ cell tumor. These results are in accordance with the results obtained with different cancer cells, such as ovarian cancer, breast cancer, glioma, lung cancer, colorectal cancer cells and laryngeal squamous cell carcinoma cell line (Hussenet et al 2010, Lu et al 2010, Alonso et al 2011, Simoes et al 2011, Han et al 2012, Lou et al 2013, Yang et al 2014. In contrast to our result, in the human bladder carcinoma cell line ECV304 ectopic expression of SOX2, OCT4 and NANOG compromised cell motility (Zhou et al 2013), while SOX2 knockdown in U343-MG glioma cell line decreased migration in vitro, but increased the migratory capacity of cancer cells in the brain in vivo (Oppel et al 2011).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Here we demonstrate that SOX2 overexpression influences the migratory potential of NT2/D1 cells, derived from the metastasis of a human testicular germ cell tumor. These results are in accordance with the results obtained with different cancer cells, such as ovarian cancer, breast cancer, glioma, lung cancer, colorectal cancer cells and laryngeal squamous cell carcinoma cell line (Hussenet et al 2010, Lu et al 2010, Alonso et al 2011, Simoes et al 2011, Han et al 2012, Lou et al 2013, Yang et al 2014. In contrast to our result, in the human bladder carcinoma cell line ECV304 ectopic expression of SOX2, OCT4 and NANOG compromised cell motility (Zhou et al 2013), while SOX2 knockdown in U343-MG glioma cell line decreased migration in vitro, but increased the migratory capacity of cancer cells in the brain in vivo (Oppel et al 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Recent data have demonstrated that SOX2 regulates the migration and invasion of different cancer cells (Han et al 2012, Yang et al 2014. However, the role of SOX2 in the behavior of cells of the human testicular germ cell tumor is largely unknown.…”
mentioning
confidence: 99%
“…Tang et al (2013) reported that SOX2 may contribute to the malignant progression of laryngeal squamous cell carcinoma (LSCC), and present as a useful prognostic marker and a potential therapeutic target for LSCC patients. Although our previous studies have demonstrated that SOX2 correlates with laryngeal tumorigenesis and development through signal pathways, such as Phosphoinositide 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) and Wnt/β-catenin pathways (Yang et al 2014a(Yang et al , 2014b), the precise pathomechanism of SOX2 in laryngeal carcinoma is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies [18][19][20][21][22] have shown that mesenchymal stem cells have migration capability and can differentiate into nerve cells at the site of injury. In addition, MSCs can provide cytokines and growth factor in the paracrine manner to improve tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%